Implementation of Legal Substance and Sharia Values in Islamic Banking in a Muslim-Minority Region - Ingratubun, Muhammad Husni (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study aims to investigate the factors that impede the application of Islamic law in the operation of Islamic banking in a non-Muslim region in Indonesia, i.e., Papua. The readiness of human resources in Islamic banking, both in quantity and quality, to support Islamic banking operations in this specific case is not well investigated. This study employs a descriptive-analytical normative legal study, with technical analysis of primary and secondary data qualitatively. The investigation indicates that the application of Islamic law to the operation of Islamic banking has not gone well, contrary to the goal of establishing Islamic banking with a profit-sharing system. The progress of Islamic banking falls short, despite the national growth target.